Design Thinking and Gamification: User Centered Methodologies - Villegas, Eva (2019)
The article presents the analysis of two systems of participatory design that allow to understand collaborative learning as a method of creating strategies and products. Two methodologies are described in order to discuss the possibilities and challenges of its application. The text begins by defining a user experience methodology designed to create with the participation of the user and continues with the definition of Design Thinking, which enhances empathy with the user through active techniques and a proficiency created to enhance the participation of people through the game Gamification. For this, the theoretical basis of each of the systems has been taken into account, the two Frameworks on which they are based on are compared and the design of the sessions with consumers is used as a starting point. It shows a first approximation of the comparison of the two systems through the sample of frameworks in study that mixes the user experience with Gamification. Through this analysis, it is affirmed that the emotional behavior of the user is key to define strategies and products, therefore, it must be designed for the user with the user.